Penguatan Kompetensi Ekoliterasi Siswa SMP melalui Pemanfaatan E-bahan Ajar Bahasa Indonesia Bermuatan Pesisir Madura - Afiyah Nur Kayati,; Fatmawati, Ira; Syarifah, Dwi Fakihatus (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to describe the core competencies of ecoliteracy in Indonesian language e-teaching materials, with a focus on the coast of Madura. Specifically, it examines the application of e-teaching materials in Indonesian language learning, particularly in the context of the Madura coast. It seeks to enhance the ecoliteracy of junior high school students. The research method employed is a qualitative approach, utilizing data collection techniques that include interviews, observation, documentation, and questionnaires. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion. Testing the validity of the data is conducted in two ways: source triangulation and technical triangulation. The results of the research show that the application of e-teaching materials containing Madurese psychology can strengthen junior high school students' ecoliteracy competencies, both mind, heart, and hands competencies. Mind, heart, and hand can be integrated in e-teaching materials through the presentation of various text genres and modes, project-based learning activities, learning communities, reflection, and continuous evaluation. The mind can be observed through students' ability to understand ecological concepts, environmental issues, and solutions to environmental problems. Heart can be seen in an increased attitude of respect and care for the environment. Hands can be seen in students' activeness in protecting and caring for the environment. The results of the student responses were 88%, indicating that students can apply ecoliteracy competencies.